Arthroscopic Superior Capsular Reconstruction in Males Provides Superior Outcomes to Reverse Total Shoulder or Debridement for Irreparable Rotator Cuff Tears. Issue 7 (30th July 2018) - Tokish, John M.; Kissenberth, Michael J.; Shanley, Ellen; Tolan, Stefan John; Adams, Kyle J.; Alexander, Ryan; Babrowicz, Sarah A.; Hawkins, Richard J.; Thigpen, Charles A.
Objectives: Early results following arthroscopic superior capsular reconstruction(SCR) in patients with massive, irreparable rotator cuff tears are promising. However, no studies have compared patient reported outcomes between SCR or reverse total shoulder(rTSA) and rotator cuff debridement for these patients. Therefore, the purpose of this study was to compare 1-year outcomes between patients with massive irreparable rotator cuff tears who underwent a SCR, rTSA, or rotator cuff debridement with a concurrent biceps tenotomy or tenodesis. Methods: Patients(n=63) who underwent either SCR(n=21), rTSA(21), or cuff debridement(n=21) and biceps tenotomy or tenodesis for a massive, irreparable rotator cuff tear treated with a minimum 1-year follow up were retrospectively reviewed. Age, sex, BMI, smoking status, Charlson Index, Hamada classification, and ASES scores were recorded and compared using a multivariate ANOVA were used to compare between surgical approaches. A Chi Square analyses were used to compare sex distribution and the Charlson Deyo Index between groups (α=0.05). Results: Overall, patients across the 3 groups were not statistically different in age or follow up ASES score at minimum 14 month follow up ( P > 0.05). There was a significant interaction effect between surgery group and sex (P=0.02) on ASES score but not age ( P =0.08). Univariate F tests revealed that male patients who received an SCR displayed a 10-14% better outcome at follow up compared to other groups (Table 1) which exceeds the reported ASES score MCID. Conclusion: Our results show comparable results across surgical options for massive irreparable cuff tears with good patient reported outcomes. Male patients displayed clinically important greater ASES scores at 1 year follow up. Future studies should evaluate these preliminary results to assess if these preliminary results hold up at longer follow up times.